PENGEMBANGAN MODUL PERANAN EKOSISTEM MANGROVE SEBAGAI SUMBER BELAJAR BERBASIS KONSERVASI DI SMA - Cahyono, Yoan Eko; Martuti, Nana Kariada Tri (Journal of Biology Education, 2015)
Abstract Science and technology development is supported by education. SMA N 2 Pekalongan has a mangrove ecosystem that has not been used as a learning resoursce. Learning procces during this run is still centered on teachers and indoor study. The module is a source of learning that guides students to learn independently. The purpose of this study was to obtain a viable and effective of the modules for learning biology ecosystem. This study are included in research and development model with pre-experimental research designs, the sample of this study are obtained by random sampling  The modules development are through the validation phase of small-scale pilot and large scale test. Validation results for the material aspect is 84.46, for the media and presentation aspects of 87.87 and 93.47 for teacher assessment, all ratings in the category very well. Research data taken form the cognitive and affective outcomes belajarn and student responses. Analysis of learning outcomes using the t test. The results of the t test analysis showed that the effective use of learning modules. Students gave the positive response of 95.8% of the modules use the role of mangrove ecosystems as a matter of these conservation-based learning resources. Based on the results of this study concluded that the role of the module-based mangrove ecosystem conservation feasible and effective to use as a source of learning in 1st high school on biology class. Abstrak Perkembangan IPTEK didukung oleh perkembangan dunia pendidikan. SMA N 2 Pekalongan memiliki ekosistem mangrove yang belum dimanfaatkan sebagai sumber belajar. Pembelajaran yang selama ini berjalan masih terpusat pada guru dan pembelajaran di dalam kelas saja. Modul merupakan sumber belajar yang menuntun siswa untuk belajar secara mandiri. Tujuan penelitian ini adalah untuk memperoleh modul yang layak dan efektif untuk pembelajaran biologi ekosistem. Penelitian termasuk dalam  research and development dengan desain penelitian pre experimental design sampel penelitian didapat dengan random sampling. Pengembangan modul melalui tahap validasi ujicoba skala kecil dan uji skala besar. Hasil validasi untuk aspek materi adalah 84,46, untuk aspek media dan penyajian 87,87 dan penilaian guru sebesar 93,47, semua penilaian masuk dalam kategori sangat baik. Data penelitian yang diambil berupa hasil belajar kognitif dan afektif serta tanggapan siswa. Analisis hasil belajar menggunakan uji t. Hasil analisis dengan uji t menunjukkan bahwa modul efektif digunakan dalam pembelajaran. Siswa meberikan tanggapan positif sebesar 95,8% terhadap penggunaan modul peranan ekosistem mangrove sebagai sumber belajar berbasis konservasi ini.  Berdasarkan hasil penelitian dapat disimpulkan bahwa modul peranan ekosistem mangrove berbasis konservasi layak dan efektif digunakan sebagai salah satu media pembelajaran biologi materi ekosistem di SMA kelas X..